Negotiating a Personal Vocabulary of Abstraction: Representing an Artist’s Sense of Place - Sturm, Cassandra Ellen (Curtin University, 2019)
Through studio practice and exegesis, this thesis is concerned with connections between abstraction and landscape in the representation of a sense of place in art practice. It seeks ways to address the difficulties inherent in reconciling personal experience with cultural expectations or representations of places. This research explores ways in which Australian artists have engaged with varying concepts of place or landscape, from their own experiences and memories, to cultural references and mythologies.